2019
DOI: 10.1186/s11658-018-0130-0
|View full text |Cite
|
Sign up to set email alerts
|

MiR-613 inhibits proliferation and invasion and induces apoptosis of rheumatoid arthritis synovial fibroblasts by direct down-regulation of DKK1

Abstract: Background This study aimed to investigate the effects of miR-613 on the proliferation, invasion and apoptosis of rheumatoid arthritis synovial fibroblasts (RASFs). Methods Synovial tissue samples were collected from 20 rheumatoid arthritis (RA) patients and 10 patients with joint trauma undergoing joint replacement surgery. The RASFs were isolated and cultured. MiR-613 and DKK1 expression in both synovial tissues and cells was detected using quantitative real-time PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 37 publications
0
20
0
2
Order By: Relevance
“…Such cellular events are mainly mediated through excessive release of inflammatory cytokines and RANKL that elevate the proteolytic activity of osteoclasts at the joint 59 . The Wnt1/β‐catenin signalling is known to be naturally suppressed by both LRP inhibitor (Dickkopf homolog 1 [DKK1]) and Dvl‐1 inhibitor (CYLD; a cell cycle regulator) that lead to the dormancy of β‐catenin inside the FLS cells, while are repressed in FLS cells during RA condition 60‐62 …”
Section: Berberine; a Potential Adjuvant For Ra Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Such cellular events are mainly mediated through excessive release of inflammatory cytokines and RANKL that elevate the proteolytic activity of osteoclasts at the joint 59 . The Wnt1/β‐catenin signalling is known to be naturally suppressed by both LRP inhibitor (Dickkopf homolog 1 [DKK1]) and Dvl‐1 inhibitor (CYLD; a cell cycle regulator) that lead to the dormancy of β‐catenin inside the FLS cells, while are repressed in FLS cells during RA condition 60‐62 …”
Section: Berberine; a Potential Adjuvant For Ra Managementmentioning
confidence: 99%
“…Such cellular events are mainly mediated through excessive release of inflammatory cytokines and RANKL that elevate the proteolytic activity of osteoclasts at the joint. 59 The Wnt1/β-catenin signalling is known to be naturally suppressed by both LRP inhibitor (Dickkopf homolog 1 [DKK1]) and Dvl-1 inhibitor (CYLD; a cell cycle regulator) that lead to the dormancy of β-catenin inside the FLS cells, while are repressed in FLS cells during RA condition [60][61][62]. Recent research reveals that berberine suppresses the Wnt1/βcatenin signalling in AAFLS cells by decreasing the levels of FZD4, LRP5 and Dvl-1 via inducing CYLD, which result in the decreased levels of β-catenin.…”
mentioning
confidence: 99%
“…До останнього часу не піддавалась сумніву виправданість хірургічної тактики при паранеф-ральному абсцесі. Однак, з удосконаленням методів візуалізації та впровадженням у клінічну практику малоінвазивних технологій відкриваються нові перспективи у лікуванні зазначених хворих [4,5].…”
Section: Discussionunclassified
“…При РА головним місцем синтезу як основних прозапальних, так і деяких протизапальних цитокінів є синовіальна тканина, водночас їх концентрація зростає і в синовіальній рідині. Головними їх продуцентами є макрофаги, фібробласти і Т-клітини [5]. Зв'язування цитокінів із рецептором через ряд проміжних стадій призводить до активації транскрипції виділених генів.…”
Section: актуальністьunclassified
“…In a recent study based on indigenous North Americans, Anaparti et al have shown an altered expression of several microRNAs in blood samples of RA patients as well as their FDRs, compared to healthy controls (HCs) [5]. Several other studies have similarly identified a dysregulated expression of microRNAs within the inflamed joints [7][8][9][10] and serum [11] as well as peripheral blood mononuclear cells (PBMCs) [12] from patients with RA, indicating that microRNA might have a role in the pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 98%